ANALISIS PENGARUH TINGKAT PENGANGGURAN TERBUKA, INDEKS PEMBANGUNAN MANUSIA, UPAH MINIMUM KABUPATEN, DAN JUMLAH PENDUDUK TERHADAP TINGKAT KEMISKINAN DI PROVINSI JAWA TENGAH - Sekar Ayu Permatasari (LP2M Universitas Bina Bangsa, 2024)
An international problem that must be addressed by various countries, especially countries with low levels of material welfare such as Indonesia, is poverty. Poverty alleviation is one of the problems that receives special attention in the Sustainable Development Goals (SDGs). When compared to other Javanese provinces, poverty in Central Java is considered quite high. Thus, Central Java Province needs to promote effective and comprehensive poverty alleviation efforts. The data of this study are numeric (in the form of numbers) so that they use quantitative methods and are processed with statistical analysis to determine the impact of the open unemployment rate, human development index, minimum wage and population on the poverty rate in Central Java Province during 2020-2023, with case studies in 35 regencies/cities in Central Java Province. The data collected is secondary data from the publication of the Central Statistics Agency. Based on the results of the study, it states that the variables of the open unemployment rate, human development index and population have a negative relationship and on the poverty rate. While the one that has a positive relationship to the poverty rate is the district minimum wage variable. Then the variables that have a significant impact on the poverty rate are the human development index and minimum wage. Meanwhile, the open unemployment rate and population size do not have a significant impact on the poverty